ANALISIS PENGARUH DESAIN HEATSINK TERHADAP EFISIENSI PANEL SURYA MENGGUNAKAN METODE COMPUTATIONAL FLUID DYNAMIC (CFD) - Ari Irawan (ELEMEN : JURNAL TEKNIK MESIN, 2025)
The growing demand for energy aligns with the increasing intensity of human activities. Most energy currently relies on non-renewable fossil fuels such as oil, coal, and natural gas, which will eventually deplete if continuously used. Renewable energy serves as a potential alternative to address this issue, one of which is solar energy. Solar energy can be converted into electricity using solar panels, which currently have an efficiency of 14–20% at 25°C. However, every ±1°C temperature increase reduces solar panel efficiency by 0.5%. To mitigate this issue, a cooling system is required to lower the temperature of the solar panels. One such cooling method is passive cooling using heatsinks. This study aims to analyze various heatsink designs that achieve the most significant temperature reduction in solar panels and examine the impact of these designs on solar panel efficiency. The method used in this research is Computational Fluid Dynamics (CFD). The heatsink design variations studied include wave-shaped, square, and triangular designs made from aluminum, copper, and an aluminum-copper alloy. The solar panels used have capacities of 50 WP, 100 WP, and 120 WP. The results show that a 50 WP solar panel equipped with a wave-shaped heatsink made of copper achieves the lowest temperature, 45.85°C, with the smallest efficiency reduction of 13.44%.